2021
DOI: 10.1177/21582440211067235
|View full text |Cite
|
Sign up to set email alerts
|

Linking Mentoring and Job Search Behavior: A Moderated Mediation Model

Abstract: The present research aims to explore the impact of mentoring relationship on college graduates’ job search behavior among Chinese undergraduate students by examining the mediator of job search intention and the moderator of job search self-efficacy. A two-wave survey study was conducted in China ( N = 594). Our findings show a positive indirect relation between mentoring and college graduates’ job search behaviors through job search intention. The graduates’ job search self-efficacy positively moderated the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For example, the analysis of 651 college students from six provinces in China revealed that self-efficacy had a positive prediction on employability (Wang D. et al, 2022). Based on the previous studies, those with higher levels of self-efficacy would rise to the challenges in the process of acquiring knowledge and skills (Ayllón et al, 2019), have greater confidence in hunting for jobs upon graduation (Lian et al, 2021), and become more employable in the labor market (Wang D. et al, 2022). Therefore, Hypothesis 3 was put forward: H3: College students' self-efficacy positively predicts their employability.…”
Section: Self-efficacymentioning
confidence: 99%
“…For example, the analysis of 651 college students from six provinces in China revealed that self-efficacy had a positive prediction on employability (Wang D. et al, 2022). Based on the previous studies, those with higher levels of self-efficacy would rise to the challenges in the process of acquiring knowledge and skills (Ayllón et al, 2019), have greater confidence in hunting for jobs upon graduation (Lian et al, 2021), and become more employable in the labor market (Wang D. et al, 2022). Therefore, Hypothesis 3 was put forward: H3: College students' self-efficacy positively predicts their employability.…”
Section: Self-efficacymentioning
confidence: 99%
“… Wang et al (2022) found that self-efficacy was positively related to the levels of employability among college students in a quantitative study across six provinces in the Chinese mainland. A higher level of self-efficacy tends to make students more confident in seeking jobs when they graduate ( Lian et al, 2021 ) and more employable in the job market ( Chow et al, 2019 ). Thus, Hypothesis 3 was proposed:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It reflects an individual’ beliefs about his or her ability to take actions, accomplish tasks, and reach goals under different situations ( Bandura, 1986 ). Previous research revealed that achievement motivation and self-efficacy were significantly correlated ( Rui et al, 2011 ; Sabti et al, 2019 ), and self-efficacy was tested to have significant and positive influence on employability ( Lian et al, 2021 ). However, the majority of these studies concentrated on exploring the impact of self-efficacy on employability through the mediation of achievement motivation ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%